2012
DOI: 10.1177/0899764012467230
|View full text |Cite
|
Sign up to set email alerts
|

National Giving Campaigns in the United States

Abstract: This study presents a narrative history and quantitative analysis of national campaigns in the United States, and analyzes how successful campaigns provide entertainment, foster empathy, and develop a national peer group with norms and networks that encourage giving. Our historical survey found that charity telethons flourished in the 1960s and 1970s, but changes in tax regulations and competition from other networks and cable television led most of them to discontinue operations in the 1980s and 1990s. In rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This has merit, given previous research pointing to an individual's political allegiances and policy attitudes influencing donation choices (Atkinson, 2009;Brooks, 2004), with Wiepking (2010) suggesting donors with liberal, left-leaning political attitudes being inclined to support international initiatives. In contrast, feelings of national group membership identified through focused-group research (Stevenson & Manning, 2010) and personal identification with charity beneficiaries (Einolf et al, 2013) underpin relatively greater donor support for charities with domestic outcomes, supported significantly through media exposure and investment in fundraising. Political attitudes, alongside specific sociodemographic characteristics have been identified as relevant to whether an individual chooses to support international causes ahead of domestic alternatives with 'political awareness' being highlighted (Rajan et al, 2009).…”
Section: Antecedents To Charitable Donation (And Intention)mentioning
confidence: 99%
“…This has merit, given previous research pointing to an individual's political allegiances and policy attitudes influencing donation choices (Atkinson, 2009;Brooks, 2004), with Wiepking (2010) suggesting donors with liberal, left-leaning political attitudes being inclined to support international initiatives. In contrast, feelings of national group membership identified through focused-group research (Stevenson & Manning, 2010) and personal identification with charity beneficiaries (Einolf et al, 2013) underpin relatively greater donor support for charities with domestic outcomes, supported significantly through media exposure and investment in fundraising. Political attitudes, alongside specific sociodemographic characteristics have been identified as relevant to whether an individual chooses to support international causes ahead of domestic alternatives with 'political awareness' being highlighted (Rajan et al, 2009).…”
Section: Antecedents To Charitable Donation (And Intention)mentioning
confidence: 99%
“…Donors feel a moral obligation to assist co-nationals (Stevenson and Manning 2010), which should lead to increased donations for domestic causes (Einolf et al 2013). The idea that donor preferences may be driven by membership of and attachment to national groups aligns closely with notions of national identity.…”
Section: Donating To Domestic Versus International Causesmentioning
confidence: 99%
“…Stevenson and Manning (2010) have previously acknowledged that membership of national groups may relate to charitable giving. It has been argued that donors feel greater empathy towards beneficiaries they personally identify with (Einolf et al 2013). Such a ''sense of fit'' (Sargeant and Woodliffe 2007) with beneficiaries may arise from nationality, one of the strongest forms of ingroup attachment (Schatz et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Brown and Minty (2008) showed that both the number of minutes of nightly news coverage and the number of words dedicated to print news of the Indian Ocean tsunami on 26 December 2004 were positively correlated with the value of donations received by five major relief organisations. Einolf, Philbrick, and Slay (2013) also report a positive correlation between the extent of media coverage of 19 national fundraising campaigns in the United States and the amount of money they raised. Together, these studies demonstrate that fundraising outcomes will be positively associated with the extent of media coverage a disaster receives—as long as people are paying attention to the news coverage (see Bennett and Kottasz, 2000; Martin, 2013).…”
Section: Introductionmentioning
confidence: 97%